English Student Teachers’ Engagement in Reflective Practice During Microteaching: Perspectives and Experience - Marlina, Neni; Ruslan, Ruslan; Sri, Melisa (Siliwangi University, 2024)
This study scrutinizes the process of reflective practices carried out by English student teachers in their microteaching practices. The focus of this study exposes the student teachers’ engagement when they implement reflective practice. Student teachers’ challenges that they face during the process of reflection and teaching practices are also revealed. This study is a qualitative case study that involved 5 English student teachers consisting of 1male student and 4 female students who enrolled in Microteaching class. They experienced microteaching practices and went through several stages: planning, teaching, feedback, re-planning, re-teaching, and re-feedback. To gain the data, student teachers’ interviews and their reflective journals were used to dig for information about their engagement in reflective practice during their microteaching and also information about their challenges in this process. The data from interviews and reflective journals were analyzed qualitatively and revealed that the student teachers showed their active participation during the reflective practice in microteaching. They experienced how reflective practices gave them opportunities to learn how to evaluate their teaching practice. However, they also faced some challenges such as particularly in critically evaluating their practices. The results of this study are expected to increase student teachers’ awareness and knowledge and their professional skills as prospective teachers. In addition, the results of this study can explore the challenges and opportunities experienced by them as a reference for improvement in implementing reflective practice and microteaching.Keywords: Student Teachers' Engagement, Reflective Practice, Microteaching